(untitled) (EU and comparative law issues and challenges series (ECLIC), 2019)
The authors in this article primarily seek to clarify the functioning of the legal and economic factors for the future integration of Bosnia and Herzegovina into the European Union. Accordingly, under the conditions of modern market and technological change, it is difficult to imagine the integration process in the sense of globalization, without the more active role of developed countries to assist countries in transition on their European path. Thus, diplomacy has a major impact on economic and legal and political integration in the EU, and on the other hand, Bosnia and Herzegovina has a political, legal and economic interest in joining the EU, and has already started using EU funds according to programs, based on the Framework Agreement between the EU and Bosnia and Herzegovina. It is quite logical that the EU funds are invested with intention to create a competitive B&H economy for the EU Single Market (internal market). However, economic co-operation is only the “first pillar” of the European integration process. A big step forward, with regard to foreign-political cooperation and security, was achieved through the Maastricht Agreement, by introducing the “second pillar” within the European Union. So, it is quite logical to conclude that the Maastricht Agreement joined the security to the Foreign Policy, which then allowed Member States to actively and unreservedly support the realization of the “second pillar”. The foreign policy and security of the EU member states cannot be at an adequate level if no internal security is established in each country. For this reason, it is very important to establish appropriate judicial cooperation and cooperation between the police, in the creation of a European judicial space, whose constituent part Bosnia and Herzegovina tend to be a part of. In this way, a “third pillar” of co-operation in the field of law and internal affairs is created.